KEPEKAAN PASTORAL KONSELING BAGI PELAYAN GEREJA KONTEMPORER - Yohan Brek (POIMEN Jurnal Pastoral Konseling, 2020)
This research is focused on a scientific study of the Pastoral Sensitivity of Counseling for Contemporary Church Servants at GMIST Filadelfia Manado. Researchers see the lack of understanding of church servants to carry out pastoral counseling services properly. Therefore this study aims; a) To explore the understanding of the Pastoral Sensitivity of Counseling for Contemporary Church Servants, b). To explore the implementation of the Pastoral Sensitivity of Counseling for Contemporary Church Ministers and c). To explore the meaning derives from the Pastoral Sensitivity of Counseling for Contemporary Church Ministers. This study uses a qualitative approach with scientific descriptive methods to be a valid way of research and data analysis in connection with finding conclusions from the results of the research conducted.